Features of non-Hodgkin's lymphoma diagnosed in minor salivary gland biopsies from primary Sjögren's syndrome patients. (23rd December 2021) - Parreau, Simon; Nocturne, Gaétane; Mariette, Xavier; Burroni, Barbara; Lazure, Thierry; Besson, Florent L; Régent, Alexis; Mouthon, Luc; Terrier, Benjamin; Seror, Raphaele; Le Guern, Véronique
Abstract: Objective: To evaluate the contribution of minor salivary gland biopsy (mSGB) histology in diagnosing primary SS (pSS)-associated non-Hodgkin B-cell lymphoma (NHL). Methods: pSS patients with mSGB at NHL diagnosis were included. Results: Among the 24 patients (92.3% female, mean age 61.3 years) with an mSGB at NHL diagnosis, 13 (54.2%) had mSGB histology–revealed NHL (mSGB + ); it was the only site enabling NHL diagnosis in 10/13 (76.9%) patients. Mucosa-associated lymphoid tissue (MALT) lymphoma was found in 23/24 (95.8%) patients; 100% of mSGB + identified MALT lymphomas. pSS and lymphoma characteristics were comparable for mSGB + and mSGB − patients. Eight (61.5%) of the 13 mSGB + patients and all 11 mSGB − patients were treated for lymphoma. Between diagnosis and 1 year of follow-up, the ESSDAI without the NHL item remained stable (7.4 vs 5.0; P  = 0.33) for the five untreated patients, while it decreased significantly for the 19 treated patients (15.8 vs 5.1; P  = 0.004). Conclusion: For pSS patients with suspected NHL, mSGB histology enabled NHL diagnosis in half of them, MALT was found in 95.8% and all mSGB + were MALT lymphomas, thereby avoiding more invasive biopsy. Our results suggest that mSGB should be obtained at pSS diagnosis and repeated during follow-up when NHL is suspected.